Characterization of Axial Forces to the Head During Kipping Handstand Push-ups - Geoffrey M Bove (CV. FOUNDAE, 2025)
Background: Thousands of athletes perform kipping handstand push-ups (kHSPUs). The safety of kHSPUs has been questioned because of vertical impacts upon the head, but no previous study has examined the ground reaction forces sustained during these exercises.Aims: This exploratory, observational cross-sectional study measured the forces exerted on the head and supported by the neck during kipping handstand push-ups (kHSPU). The goal was to compare these forces with known thresholds that can damage the cervical spine. The researcher also aimed to determine how often people experience symptoms after performing these exercises.Methods: Sixteen volunteers performed three sets of up to 7 kHSPUs with their head and one hand contacting force platforms. Force and video recordings were made while performing the exercises. Volunteers were asked if they had neck pain or headaches related to the exercises.Result: Force profiles showed distinct landing and kipping peaks. Landing forces were higher than during a headstand but less than body weight. Forces were greatest during the